Simple Method to Evaluate Strength and Relaxation Properties of Asphalt Binders at Low Temperature. Issue 6 (June 2019) - Matias De Oliveira, Jhenyffer; Yan, Tianhao; Turos, Mugurel; Ghosh, Debaroti; Van Deusen, Dave; Marasteanu, Mihai
Low temperature cracking represents the main distress in asphalt pavements built in cold regions. During the Strategic Highway Research Program (SHRP) two test methods were developed to investigate the low temperature behavior of asphalt binders: bending beam rheometer (BBR) and direct tension tester (DTT). In this research, a simple testing protocol developed to obtain failure properties of asphalt binders at low temperatures is used to characterize the behavior of five asphalt binders used in the construction of MnROAD test cells in 2016. It is shown that a combination of creep followed by strength testing provides a more complete picture of the low temperature properties of asphalt binders and can improve the selection process. Binders with similar creep and relaxation properties have significantly different failure properties. It is also demonstrated that BBR strength data is obtained under linear viscoelastic conditions for the entire duration of the test and that creep and strength data can be interconverted using linear viscoelasticity.